L’ÉCRITURE DE L’ITALIE CHEZ DOMINIQUE FERNANDEZ : SACRALISATION D’UN ESPACE PROFANE - Maroua DEROUICHE (Studia Universitatis Babeş-Bolyai. Philologia, 2021)
Italy in the Writings of Dominique Fernandez: The Sacralization of a Profane Space. For Dominique Fernandez, writing about Italy is associated with a quest for original androgyny. The Italian space supports a return to a primitive existence. Synonymous with freedom and sexual undifferentiation, it allows us to find prelapsarian paradise, where the boundaries between the sexes did not exist. Mircea Eliade’s works follow the same logic. Indeed, the author studies the nostalgia for the origins which incites man to discover the mythical primordial era sanctified by the gods. Hence, this article blends the historical-religious endeavor with the literary approach which, though unable to go back in time, keeps repeating it indefinitely, thanks to the demiurgic power of the writer.